EFFICACY OF AQUEOUS AND POWDERED LEAF EXTRACTS OF Chromolaena odorata (ASTERALES: ASTERACEAE) AND Ficus mucuso (ROSALES: MORACEAE) BOTANICALS ON ROOT-KNOT NEMATODE INFECTING WATERMELON IN KWARA STATE, NIGERIA - Oluropo Ayotunde APALOWO; Nkechi Betsy IZUOGU; Halimat Shola BABA; Isaiah Olusesan ADEPOJU; C. M. OLAJIDE; Muhammed Adewole ADEYEMI; Olusegun Samuel BALOGUN (Journal of Applied Life Sciences and Environment)
Watermelon production in Kwara State, Nigeria, is affected by root-knot nematode (RKN), as all varieties of the crop are susceptible. The aim of this study was to identify readily available and environmentally safe nematicides for the management of RKN. The field was located at the Teaching and Research Farm of the University of Ilorin and set out in a randomised complete block design, with four replications. Aqueous and powdered extracts of Chromolaena odorata (L) King and Robinson and Ficus mucuso Welw. ex Ficalho were applied alone and in combination. There were seven total treatments: C. odorata aqueous, F. mucuso aqueous, C. odorata powder, F. mucuso powder, C. odorata and F. mucuso aqueous, C. odorata and F. mucuso powder, and the control. Data were collected on growth, yield and nematode populations. All data collected were subjected to analysis of variance, and treatments were compared using Duncan’s multiple range test at a 5% level of significance. The essential oil of each botanical was determined using gas chromatography-mass spectrometry. The vine length (185.61) and yield (2401.05) of plants treated with botanicals were significantly higher than those of the control at P<0.005. The nematode population was also significantly lower in plants treated with botanicals than in the control (318.30 and 230.00, first and second year, respectively) at P<0.005. Among the treatments, the combination of C. odorata and F. mucuso powders was the most effective, with higher growth and yield performance. The experiment showed that aqueous and powdered extracts of C. odorata and F. mucuso were effective in managing RKN in the field.